A few problems in the generic nomenclature of insects and amphibians, with recommendations for the publication of new generic nomina in zootaxonomy and comments on taxonomic and nomenclatural databases and websites - Dubois, Alain (Zootaxa, 2017)
Dahanukar et al. (2016a) proposed the nomen Walkerana for a new genus of amphibians, but shortly after (2016b) they replaced it by the new nomen Sallywalkerana, believing that their nomen Walkerana was preoccupied by a generic nomen of orthopterans. This was unjustified because the orthopteran nomen ‘Walkerella’ Otte & Perez-Gelabert, 2009a and its new replacement nomen ‘Walkerana’ Otte & Perez-Gelabert, 2009b were both nomina nuda. These recent examples of nomenclatural errors in generic nomenclature are just a few among many in recent zootaxonomic publications. This opportunity is taken to make some general methodological recommendations, in several domains (availability, homonymy, synonymy, neonymy, length and palatability of nomina), for the publication of new generic nomina in zootaxonomy. However, the absence of a comprehensive database and website providing all the relevant information necessary to establish the nomenclatural status of all zoological generic and subgeneric nomina is a brake on the efforts that can be made to avoid nomenclatural errors in zoological generic nomenclature. The international community of taxonomists should seek at establishing such a database and website.